1982
DOI: 10.1111/j.1432-1033.1982.tb06825.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Caffeine on Glucose‐Induced Inactivation of Gluconeogenetic Enzymes in Saccharomyces cerevisiae

Abstract: The mechanism of catabolite inactivation of three gluconeogenetic enzymes, fructose-l,6-bisphosphatase, cytoplasmic malate dehydrogenase and phosphoenolpyruvate carboxykinase, has been studied in the yeast Saccharomyces cerevisiae. The glucose-induced inactivation of the three enzymes is remarkably retarded by preincubation of the cells with different caffeine concentrations; however, a full conservation of activity has never been obtained, even at the highest drug concentration. Caffeine modifies the metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

1983
1983
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 38 publications
1
21
0
Order By: Relevance
“…Whereas the mutant AM3-4B showed the reported rise in the cyclic nucleotide [ 14,171, in the adenylate cyclase-defective mutant, AM7-1 lD, low and constant levels of CAMP were measured throughout the experiment. Such levels are probably due to contaminating extracellular CAMP present in the growth medium.…”
Section: Resultsmentioning
confidence: 99%
“…Whereas the mutant AM3-4B showed the reported rise in the cyclic nucleotide [ 14,171, in the adenylate cyclase-defective mutant, AM7-1 lD, low and constant levels of CAMP were measured throughout the experiment. Such levels are probably due to contaminating extracellular CAMP present in the growth medium.…”
Section: Resultsmentioning
confidence: 99%
“…Mannose and raffinose were also effective but gave rather variable results (not shown). Tortora et al (1982) observed that the DNA-stacking drug caffeine inhibits the glucoseinduced increase of the cAMP level and decrease of the fructose-1 ,&bisphosphatase activity in a very similar way. In the course of experiments on the long-term effects of RNA synthesis inhibitors on glucose-induced activation of trehalase, we discovered that the DNA-stacking drugs ethidium bromide, acridine orange and acriflavine caused short-term inhibition of the activation of trehalase.…”
Section: Sugar-induced Trehalase Activationmentioning
confidence: 91%
“…The activity of trehalase (reviewed by Thevelein, 1984a) and fructose-l,6-bisphosphatase (reviewed by Holzer, 1984) is regulated by CAMP-dependent protein phosphorylation. The activity changes of both enzymes are preceded by a rapid, transient increase of the cAMP level (Van der Plaat, 1974;Mazon et al, 1982;Purwin et al, 1982;Tortora et al, 1982;Thevelein, 1984a).…”
Section: Introductionmentioning
confidence: 99%
“…Assay O f c A M P Intracellular CAMP concentration was determined with a test kit from Boehringer (Mannheim, FRG) according to the method of Tortora et al [21].…”
Section: Assay Of Glucose Uptakementioning
confidence: 99%